Squalene from Fish: The Natural Shield Against Heart Disease - Venkat, Chundru Sri Sai; Nagendrasai, Kurapati; Mounika, Islavath; Sravani, Guntapalli; Sindhuja, Pothula (Chronicle of Bioresource Management, 2025)
Squalene, a naturally occurring triterpene, has gained significant attention for its potential cardiovascular protective effects, particularly when derived from fish sources. Fish-derived squalene, especially from deep-sea fish such as sharks and certain species of tuna and sardines, is rich in bioactive compounds that contribute to its therapeutic properties. This article explores the mechanisms through which squalene exerts cardioprotective effects, including its antioxidant activity, cholesterol regulation, anti-inflammatory properties, and ability to improve blood circulation and lower blood pressure. Scientific studies have demonstrated that squalene supplementation can reduce levels of LDL cholesterol and triglycerides, enhance HDL cholesterol, and decrease oxidative stress, all of which are key factors in preventing cardiovascular diseases (CVDs). Despite its potential, careful consideration of potential side effects, such as allergies or gastrointestinal discomfort, is necessary. Overall, fish-derived squalene presents a promising natural supplement for cardiovascular health, offering a safe and effective means of reducing CVD risk.